Analisis Penyakit Tuberkulosis (TBC) pada Provinsi Jawa Timur Tahun 2021 Menggunakan Geographically Weighted Regression (GWR) - Rahmawati, Novi; Karno, Faldianus; Hermanto, Elvira Mustikawati Putri (Indonesian Journal of Applied Statistics, 2023)
Tuberculosis (TB) is an infectious disease with the highest mortality rate in the world. In East Java, TB cases will experience a significant increase in 2021. This study uses the Geographically Weighted Regression (GWR) method to analyze the variables that affect TB cases in East Java that year. The variables used are the number of TB cases, the number of smokers, the number poor population, and population density. The GWR results show that the number of poor people has a significant effect on all districts/cities in East Java. Meanwhile, population density has a significant effect in most areas (except Pacitan, Bondowoso, Situbondo). This research provides input for the government to reduce the number of TB cases in East Java. Efforts need to be made to increase employment and reduce regional disparities so that the burden of this disease can be controlled more effectively.Keywords: TBC, GWR, Kernel Bisquare